Estudio de factibilidad para la exportación del vino de agraz a los Estados Unidos (2022)
This project seeks the development and analysis of Agraz wine as a product to be exported. Colombia has ideal climatic and land conditions for the harvest of specific products, which would be complex to produce in other countries, due to its topographical and geographical location